SAFAYÎ WHO IS FROM SINOP, HIS LIFE, HIS WORKS AND THE FETIHNAME OF INEBAHTI AND MOTON (PALIMPSEST / ПАЛИМПСЕСТ, 2016)
Fetihnames are historical and literary works about conquest of a place and these works could also denote verse or prose. Fetihnames are significant in terms of historical and literary value. In the Ottoman Empire, during II.Bayezid period Ottoman Navy was quite empowered and conquered many places with a naval battle. Sinoplu Safayi who wrote İnebahtı and Moton fetihname’s, also participated in the conquest of İstanbul. Safayi lived in the period of Fatih Sultan Mehmet, II. Bayezid, Yavuz Sultan Selim and Sultan Suleyman. II. Bayezid was conquered in many places during the naval battle with the Ottoman navy which was quite strong. Safayi was a sailor and a poet and he participated in the conquest of İnebahtı and Moton-Koron. Describing the war by a person living after the conquest of Inebahtı and Moton, increases the value of the work. In this article Safayî's life provides information about his work ‘Fetihname of Inebahtı and Moton’.